Increased circulating polymorphonuclear myeloid-derived suppressor cells are associated with prognosis of metastatic castration-resistant prostate cancer - Kobayashi, Takuro; Nagata, Masayoshi; Hachiya, Tsuyoshi; Wakita, Haruhiko; Ikehata, Yoshihiro; Takahashi, Keiji; China, Toshiyuki; Shimizu, Fumitaka; Lu, Jun; Jin, Yiming; Lu, Yan; Ide, Hisamitsu; et al. (Frontiers in Immunology, 2024)
Introduction Myeloid-derived suppressor cell (MDSC) exhibits immunosuppressive functions and affects cancer progression, but its relationship with prostate cancer remains unclear. We elucidated the association of polymorphonuclear MDSC (PMN-MDSC) and monocytic MDSC (M-MDSC) levels of the total peripheral blood mononuclear cells (PBMCs) with prostate cancer progression and evaluated their roles as prognostic indicators. Methods We enrolled 115 patients with non-metastatic hormone-sensitive prostate cancer (nmHSPC, n = 62), metastatic hormone-sensitive prostate cancer (mHSPC, n = 23), and metastatic castration-resistant prostate cancer (mCRPC, n = 30). Subsequently, the proportions of MDSCs in each disease progression were compared. Log-rank tests and multivariate Cox regression analyses were performed to ascertain the associations of overall survival. Results The patients with mCRPC had significantly higher PMN-MDSC percentage than those with nmHSPC and mHSPC (P = 7.73 × 10−5 and 0.0014). Significantly elevated M-MDSC levels were observed in mCRPC patients aged <70 years (P = 0.016) and with a body mass index (BMI) <25 kg/m2 (P = 0.043). The high PMN-MDSC group had notably shorter median survival duration (159 days) than the low PMN-MDSC group (768 days, log-rank P = 0.018). In the multivariate analysis including age, BMI, and MDSC subset, PMN-MDSC was significantly associated with prognosis (hazard ratios, 3.48; 95% confidence interval: 1.05–11.56, P = 0.042). Discussion PMN-MDSC levels are significantly associated with mCRPC prognosis. Additionally, we highlight the remarkable associations of age and BMI with M-MDSC levels in mCRPC, offering novel insights into MDSC dynamics in prostate cancer progression.